GASTRODIPLOMASI SEBAGAI INSTRUMEN SOFT POWER (STUDI KASUS: STRATEGI NATION BRANDING MEKSIKO DAN PERU DI BENUA AMERIKA) - BR Pasaribu, Ayu Kristiani; Zulian, Ibnu (UIN Alauddin Makassar, 2026)
This research analyses the effectiveness of gastronomy as a soft power instrument in strengthening the nation branding of countries in the Americas. By focusing the study on the successes of Mexico and Peru, this research evaluates how the integration of culinary heritage into foreign policy is capable of generating measurable diplomatic influence and economic benefits. Using a descriptive qualitative method based on secondary data from UNESCO reports and the World Travel Awards, the results indicate that the designation of traditional cuisine as world cultural heritage has triggered a significant surge in the international tourism sector and food commodity exports. This study concludes that a consistent gastrodiplomacy strategy not only reinforces regional cultural identity but also functions as an effective creative economy engine in enhancing a country's geopolitical bargaining power on the global stage.